Lumbar Cistern Drainage and Gentamicin Intrathecal Injection in the Treatment of Carbapenem-Resistant Klebsiella Pneumoniae Intracranial Infection After Intracerebral Hemorrhage craniotomy: A Case Report - Zhou, Min; Liang, Richu; Liao, Quan; Deng, Pingfu; Fan, Wentao; Li, Chenzhuo (Infection and drug resistance, 2022)
Intracranial infection is a common complication caused by craniotomy. In particular, patients in Intensive Care Units (ICU) are prone to intracranial infection with multiple drug-resistant bacteria. Due to the lack of sensitive antibiotics for the treatment of multiple drug-resistant bacteria, there are few literatures focusing on the treatment of intracranial infection, and patients often fail to receive unified and standardized treatment. Consequently, patients with Carbapenem-resistant bacteria intracranial infection report poor prognosis and high mortality. It is very important to discuss how to treat patients with intracranial infection caused by multidrug resistant bacteria. We reported a case of intracranial infection of Carbapenem-resistant Klebsiella pneumoniae(CRKp) due to high flap tension, poor wound healing and CSF leakage caused by subcutaneous fluid accumulation after intracerebral hemorrhage craniotomy. Since the patient was exposed to intracranial infection resulted from subcutaneous fluid accumulation, we adopted the method of continuous drainage with subcutaneous tube. When subcutaneous effusion disappeared, the subcutaneous drainage tube was pull out, while patients exhibited high fever again, the waist big pool drainage catheter and continuous drainage were carried out. According to the result of Subcutaneous effusion and CSF culture indicated multiple drug resistant Klebsiella pneumoniae intracranial infection and drug susceptibility, The treatment of gentamicin intrathecal injection, intravenous use amikacin and oral Paediatric Compound Sulfamethoxazole Tablets was adopted, the condition of intracranial infection was eventually controlled, with the consciousness restored. This patient was characterized by intracranial infection with Carbapenem-resistant Klebsiella pneumoniae(CRKp). Subcutaneous effusion is a high-risk factor for poor wound healing and interventions are required to be conducted to promote healing as early as possible to contribute to decreasing the menace of CSF leakage. In this case, Continuous drainage and intrathecal injection of sensitive antibiotics serve as critical process to determine the best strategy for clinical treatment of intracranial infection.